(untitled) (Research, Society and Development, 2024)
Men’s Health is a topic of knowledge in scientific society, where in general, men suffer more from severe and chronic health conditions than women and die more often than women from the main causes of death. This fact can be associated with the socialization of men, in which care is not seen as a masculine practice. In view of this, research has sought to reflect on masculinity to understand the impairments to men’s health. The objective of this study was to identify whether health monitoring occurs for military firefighters in a fire station located in the interior of the state of Rio Grande do Sul. This is a qualitative, exploratory and descriptive study, and the research was carried out with 18 (eighteen) firefighters through a semi-structured interview containing 11 (eleven) questions. The importance of the study is understood to understand how men’s health is and possible strategies and health promotion in the work context of military firefighters. The results demonstrated that the majority of firefighters reported a lack of health promotion within the fire station, and that they were only offered a gym to carry out physical activities. In the rest, agreements are offered with institutions such as health plans for scheduled care. We conclude that there is a lack of actions aimed at promoting men’s health for these professionals within the barracks and that a careful look at them is necessary, as this profession involves responsibility focused on life. We also highlight the continuity of studies that promote this topic, thus aiming to improve the quality of life of these professionals.